Comedy and Tragedy in the Andean Commons - Paul Trawick (Journal of Political Ecology, 2002)
In the Andes of Peru a familiar story has unfolded in many communities around the sharing and use of water, a tragedy often attributed to an irresolvable conflict between the inherently selfish interests of the individual and the cooperative needs of the group. This article traces the history of irrigation in one highland valley based on comparative ethnographic research, examining the reasons for both success and failure in governing the commons and trying to explain why the former has given way to the latter in many, but by no means all, places. It reveals that success can be relatively unproblematic and was once widespread at the local level, and that failure has occurred where institutional arrangements have been imposed that, according to the conventional theory, should have prevented the tragedy instead of bringing it about: privatization of the resource, on the one hand, and State control of it on the other. Where selfishness and discord have prevailed they are driven by an apparent water scarcity that is socially constructed, the product of a new political ecology imposed initially by the local elite and then dominated by them with the State’s help, at the expense of the peasantry. The author argues that, far from being inevitable, the tragedy of the commons in water management can be avoided, arrested, and perhaps even reversed, in the Andes and other arid and mountainous parts of the world.